Praktik Pembagian Harta Warisan Ditinjau Dari KHI - Karmila Karmila; Syapar Alim Siregar (UIN Syekh Ali Hasan Ahmad Addary Padangsidimpuan, 2021)
The basic problem in this research is regarding the practice of distributing inheritance in Nagari Lansek Kadok, South Rao District, Pasaman Regency, West Sumatra Province. This problem is motivated by the practice of inheritance distribution that girls get more inheritance than boys. Whereas the community in Nagari Lansek Kadok, South Rao District, Pasaman Regency, West Sumatra Province, the majority are Muslim with a population of 2,250 families of which there are 1,350 families if it is divided into 60% who are not subject to the practice of dividing inheritance into 2 parts and women 1 part.The results of this study are,, the firstly reason why the people in Nagari Lansek Kadok practice the distribution of inheritance for men 1 part and women 2 parts, the reason is because the people in Nagari Lansek Kadok use matrilineal customs which divide inheritance from the mother's lineage which makes the difference, namely because in In practice, women in Nagari Lansek Kadok receive more inheritance than men, while the share of pusako received by boys is the traditional sako title passed down from mamak to nephews. In addition to serving as the successor of women's descendants in Minangkabau, their existence is highly respected and also involved in deliberation in the family and village. the second purpose of compiling Islamic law in the practice of dividing inheritance, while the inheritance system in the Compilation of Islamic Law (KHI) refers to the heirs by referring to faraidh, namely bilateral inheritance, meaning that men and women have the same right to inherit from the heir.